Design of a teaching smart prototype product - Phua, Tian Soon. (2008)
The purpose of this project is to propose a smart pedagogical model for the Industrial Design (ID) students at Nanyang Polytechnic’s School of Design. The reason is to allow the students to learn qualitative design enhancement through a hands-on implementation with sufficient exposure to creative synthesis, multidisciplinary problems, teamwork, total design and the need to balance the making of models or products with critical thinking.